PERBANDINGAN KOMPONEN MUTU LAYANAN KLINIS RAWAT JALAN PUSKESMAS AKREDITASI DAN NON AKREDITASI MENGGUNAKAN KERANGKA KERJA MALCOLM BALDRIGE FRAMEWORK - Saragih, Mery Nurlinda Th; W, Balqis; Bangun, Sri Melda Br. (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
The Community Health Center still encounters various obstacles in carrying out accreditation, especially in the quality of outpatient clinical services, including differences in information related to post-failure measures in previous accreditation assessments, lack of special resources from staff availability, and sudden submission and assessment processes. This can be studied based on the framework of the Malcolm Baldrige Framework. The purpose of this study was to compare the quality components of outpatient clinical services at accredited health centers and non-accredited health centers using the Malcolm Baldrige Framework. This research is an analytic observational study with a cross-sectional design approach. The research was conducted in Silou Kahean District, Simalungun Regency, namely the accredited public health center (Puskesmas Negeri Dolok) and the non-accredited health center (Puskesmas Sinasih). The study population was 106 people, the sample was taken entirely (total sampling). Data analysis used univariate analysis, bivariate analysis used independent sample t-test with a 95% confidence level ( = 0.05). The results showed that there were differences in the quality of outpatient clinical services at accredited public health centers (Puskesmas Negeri Dolok) and non-accredited health centers (Puskesmas Sinasih) using the Malcolm Baldrige Framework in Silou Kahean District, Simalungun Regency (p=0.000; t=4.976), as well as components namely leadership (p=0.000; t=4.082), strategic planning (p=0.000; t=4.998), customer focus (p=0.003; t=3.048), knowledge management (p=0.002; t=3.222), focus workforce/employees (p=0.027; t=2.236), focus of work operations (p=0.000; t=5.728), and outcomes (p=0.000; t=7.316).